The Influence of Price Perception, Sales Promotion, and Consumer Confidence on Pinkyshop Online Purchase Decisions at Shopee Market Place - Intan Filiana Suhendi; Elwisam Elwisam; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to analyze the influence of price perception, sales promotion, and consumer confidence on pinkyshop online purchase decisions in the shoppe marketplace. The results of the study using primary data in the form of questionnaires to 115 Pinkyshop consumer respondents showed that there was a positive and significant influence between sales promotion and consumer confidence in purchasing decisions for Pinkyshop products. And there is a non-positive and insignificant influence on the price perception variable on purchasing decisions that means if prices rise then purchasing decisions will decrease, otherwise if prices fall then purchasing decisions will increase. Even so, the prices provided at pinkyshop in the shoppe marketplace are in accordance with the quality of the product and the price is almost similar to competitors. While sales promotions carried out to provide product information to consumers can improve purchasing decisions. Consumer confidence contributes the most than price perception and sales promotion. This shows that according to consumers, trust is caused by security, the information conveyed is accurate and there are various kinds of products in it. From this study found that of the many factors that can influence the occurrence of transactions through ecommerce, the trust factor is the key factor. Only customers who have trust will dare to make transactions through internet media, thus making consumers more confident to decide to shop at pinkyshop.